1993
DOI: 10.1023/a:1018990001310
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Recombinant human macrophage colony-stimulating factor (rhM-CSF) promotes macrophage proliferation and activity. rhM-CSF clinical trials are currently in progress and require a stable, pharmaceutically acceptable dosage form. This report documents pH effects on rhM-CSF degradation profiles in aqueous solution, with an emphasis on identifying degradation products. Thus, highly purified rhM-CSF was maintained at 30 to 50 degrees C in solutions adjusted to pH 2 to 10. Stressed samples were analyzed by SDS-PAGE, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The effects of dextrose on the stability of AT1002 terminally modified peptides are shown in Figure 3 . Dextrose is a stabilizing excipient of proteins, 19 which is used as an additive for nasal administration solutions during in vivo studies. 24 Our previous report indicated that dextrose has stabilizing effects on AT1002.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of dextrose on the stability of AT1002 terminally modified peptides are shown in Figure 3 . Dextrose is a stabilizing excipient of proteins, 19 which is used as an additive for nasal administration solutions during in vivo studies. 24 Our previous report indicated that dextrose has stabilizing effects on AT1002.…”
Section: Resultsmentioning
confidence: 99%
“…Chemical degradation and protein aggregation may be induced by a variety of physical factors such as temperature and ionic strength, or with time; 18 degradation products such as C-terminal fragments can change significantly with varying pH. 19 In addition, the stability of proteins can be modified by soluble and nontoxic excipients, such as dextrose, or by changing their structural characteristics towards those of thermophilic proteins by introducing negatively charged residues at the N-cap or positively charged residues at the C-cap of the helix. 18 The latter approach is effective because the helical structure of short peptides and proteins is stabilized by capping interactions between side chains and unfulfilled peptide groups at the N- and C-termini.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the melting transition temperature ( T m ), or denaturation temperature of unfolding as it is sometimes called, can be a measure of a solution's influence on the stability of a protein ( ). The T m is related to the change in free energy between the native and denatured states of a protein molecule (i.e., Gibbs−Helmholtz equation) and, therefore, is a thermodynamic parameter of conformational stability ( , ).…”
mentioning
confidence: 99%
“…Increase in soluble aggregates can result in change in immunogenicity of the therapeutic protein. Aggregates in certain cases can be visualized e.g., insulin and IL-1β 97,98 . Insoluble aggregates can be detected by FTIR, Raman, and electron spin resonance spectroscopy, or light scattering techniques (UV absorption).…”
Section: Aggregation and Precipitationmentioning
confidence: 99%